Ventilator-associated pneumonia (VAP): a UK PICU experience. (24th May 2012) - Ismail, N; Darbyshire, A; Thorburn, K
Abstract : Introduction: Internationally there is diversity surrounding the definition, incidence and diagnostic criteria for VAP. To date, there is no published data from UK on VAP in paediatric population. Aim: To determine the incidence of VAP on a UK PICU, associated pathogens, co-morbidities, and outcome. Methods: All children mechanically ventilated for 48 hours or more from October 2010 to May 2011 (8 month period) were included. We retrospectively reviewed radiological, clinical, and microbiological data, using the CDC (Centre for Disease Control) 2001 criteria for the diagnosis of VAP. Results: Total number admitted 745, with 621 episodes of ventilation. Thirty five (5.6%) developed new radiological pneumonic changes ≥48 hours following commencement of ventilation. Median age was 6 months (range 1 day – 16 years). Male: female ratio 3:1. Median length of ventilation was 9.5 days. VAP incidence was 9.2/1000 ventilator days. Sixty three percent of these children with radiological changes fulfilled at least 3 CDC criteria for diagnosis of VAP, while nearly 77% (27/35) had a respiratory pathogen identified. (21 endotracheal aspirates or broncho-alveolar lavage and 14 sputum). All children with 4 or more CDC criteria had positive cultures. Commonest pathogens were viruses, gram positive and gram negative bacteria in 30%; 27% and 20% respectively, with the remainder being Candida and pneumocystis. There were underlying co-morbidities in 91% of cases, including cardiac (40%), respiratory (27%), infections and surgery (22%), accidents and syndromes 15% each. Outcome - 4 deaths most likely due to VAP, all had complex underlying problems and died while ventilated on PICU. The remainder was discharged. Conclusion: The incidence of VAP in this study period was 9.2/1000 ventilator days. Respiratory viruses and gram-positive bacteria are the commonest causative pathogens of VAP. Co-morbidity is a significant risk factor for VAP. VAP-associated mortality was approximately 11%. Recommendations: Routine surveillance is crucial, larger studies and uniform diagnostic criteria are needed to define the epidemiology of VAP in the UK, and accordingly to place strategies for prevention.